Sudan : First Review Under the Staff-Monitored Program. (IMF Staff Country Reports; Country Report ;, 2014)
KEY ISSUES Political Context: Sudan is embarking on a difficult national dialogue with the opposition and some armed groups in the Blue Nile and South Kordofan regions. The objective is to break the current destructive cycle of instability and prepare for the upcoming presidential election in 2015. This dialogue, if successful, could help create the conditions needed to address the challenges that emerged after the secession of South Sudan, including sustaining a much-needed broad economic recovery and adjusting the economy to its new potential. The current staff monitored program (SMP) is providing an adequate policy framework and a path in this direction. Macroeconomic situation and outlook: Tight monetary conditions and improved fiscal performance, together with lower food prices, contributed to lower inflation at end-March. However, the curb market exchange rate further depreciated against the U.S. dollar on account of the uncertainties in the oil market triggered by the South Sudan conflict, further widening the gap between the official and curb market rates to more than 50 percent. The outlook for 2014 remains broadly favorable, with growth expected to reach 2.5 percent, and inflation to continue its downward trend to about 18 percent. Program performance: Performance under the SMP through end-March 2014 was affected by adverse shocks and security spillovers. All end-March quantitative benchmarks were met, except for the ones on net international reserves and net domestic assets of the Central Bank of Sudan (CBOS). The indicative targets on social spending and the non-oil primary deficit were also missed by a slight margin. Corrective actions have been taken to ensure that these targets will be met in the second quarter. Urgent measures are needed to address the gap between the official and curb market exchange rates. The authorities have also made good progress toward meeting their end-June structural benchmarks. Risks remain large and tilted to the downside. The uncertain political transition, the volatile domestic oil market, and the fragile security environment may slow down the reform momentum. The recent peace agreement between the warring factions in South Sudan, if implemented, would improve the risk outlook.